2022
DOI: 10.1136/annrheumdis-2021-221735
|View full text |Cite
|
Sign up to set email alerts
|

Distinct impact of DMARD combination and monotherapy in immunogenicity of an inactivated SARS-CoV-2 vaccine in rheumatoid arthritis

Abstract: ObjectivesTo evaluate the distinct impact of disease modifying antirheumatic drugs (DMARD) combination and monotherapy in immune response to an inactivated SARS-CoV-2 vaccine in patients with rheumatoid arthritis (RA).MethodsThis phase 4 prospective study analysed seroconversion (SC) of anti-SARS-CoV-2 immunoglobulin G (IgG) and neutralising antibodies (NAb) induced by the inactivated vaccine (CoronaVac) in patients with RA in comparison to controls (CG). Disease activity and treatment were also assessed. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 50 publications
11
28
1
Order By: Relevance
“…We identified that prednisone in doses ≥7.5 mg/day and rituximab have a negative impact on immune response after the fourth dose in poor/non-responder patients, as also reported by our group after prime vaccination [ 7 , 10 , 17 ]. With regard to LEF, its negative effect on immunogenicity observed in the present study is probably related to the fact that all patients used this drug in association with other DMARDs, as observed in an RA population immunized with Sinovac-CoronaVac vaccine [ 7 ]. In contrast to SSc and RA, SLE patients tended to have higher rates of positive antibody responses.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We identified that prednisone in doses ≥7.5 mg/day and rituximab have a negative impact on immune response after the fourth dose in poor/non-responder patients, as also reported by our group after prime vaccination [ 7 , 10 , 17 ]. With regard to LEF, its negative effect on immunogenicity observed in the present study is probably related to the fact that all patients used this drug in association with other DMARDs, as observed in an RA population immunized with Sinovac-CoronaVac vaccine [ 7 ]. In contrast to SSc and RA, SLE patients tended to have higher rates of positive antibody responses.…”
Section: Discussionsupporting
confidence: 83%
“…The detrimental effect of immunosuppressive therapy on antibody production has been previously demonstrated in ARD patients [ 1 , 7 , 8 , 17 ]. We identified that prednisone in doses ≥7.5 mg/day and rituximab have a negative impact on immune response after the fourth dose in poor/non-responder patients, as also reported by our group after prime vaccination [ 7 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on methotrexate, JAKi, and abatacept were judged not yet consistent/robust (9). Meanwhile, more data for ABA and JAKi are coming to light from studies with sample sizes ranging to 11 to 54 patients demonstrating reduction in antibody titers (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%